Perspectives on the Great Irish Famine - Liam Kennedy; Donald M. MacRaild (Queen's University Centre for Economic History (QUCEH), 2022)
This overview of the Great Irish Famine is unfolded in terms of the three major phases of British government policy. The understanding of poverty underlying the paper is in terms of diet, not income per capita, housing or literacy, or any of the other more conventional measures in use by historians of the Famine. The claim is that reliance on a diet consisting almost exclusively of the cheapest foodstuff (potatoes) is both the definition of and the principal measure of poverty in pre-Famine Irish society. There is some emphasis on class conflict, both in its overt and its latent forms, as a constraint on the redistribution of income and food in the face of a massive crisis. A.K. Sen's entitlements thesis on the causes of famine is held to have limited usefulness for the study of the Irish Famine, and there is a renewed emphasis on the absolute shortfall in domestic food production ('food availability decline') in the later 1840s. Ever so briefly, attention is drawn to lives saved as well as lives lost.
Keywords: I38; N43; N53; Q18; 330; Great Irish Famine; poverty; entitlements; government policy